"النظام القانوني للمقاطعة الإدارية في التنظيم الإداري الجزائري " - هركوس, ياسمينة (جامعة الوادي University of Eloued, 2020)
المقاطعة الإدارية هيئة إدارية مستحدثة تندرج ضمن إطار المركزية الإدارية في صورة عدم تركيز إداري أنشأت بموجب المرسوم الرئاسي15/140 داخل بعض الولايات باتباع مجموعة من المعايير بهدف تحسين الخدمة العمومية وتقريب الإدارة من المواطن وتخفيف الأعباء على الولاية الأصلية، يسيرها الوالي المنتدب الذي يعين بموجب مرسوم رئاسي ويمارس مهامه تحت سلطة والي الولاية بمساعدة أجهزة وهياكل إدارية تتمثل في الإدارة العامة للمقاطعة الإدارية والمديريات المنتدبة ومجلس المقاطعة الإدارية وهي بذلك جزء من الولاية لا تتمتع بالشخصية المعنوية يرجع انشاءها وتعديلها وإلغائها إلى التنظيم لكن صار من الواضح بقاءها من خلال المرسوم الرئاسي 19/328 الذي استحدث 44 مقاطعة إدارية جديدة. " The District Administration is a new administrative body that falls within the framework of centralisation in the form of administrative deconcentration. It is established by the presidential decree 15-140 in some states by following a set of standards it aims at improving public service bringing the burden on the administrations closer to the citizens and reduce the burden on the original state. The.lattest is conduted by the delegated governor who is appointed by the presidential decree, He declares his functions under the authority of the state governor with the aid of administrative members and structures represented in the general administration of the administrative. District, the delegated directorates, and the Administrative District council which is thus a part of the state without the moral personality that can be established, canceled and amended by the organization. However, it becames obvious that it will last because of the presidential decree 19-328 that has introduced 44 new Administrative Districts. "
ماستر اداري
Keywords: المقاطعة الإدارية - هيئة إدارية مستحدثة; The administrative district - administrative body